2010
DOI: 10.1021/je900550v
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted Ionic Liquids for Sustainable Processes: Synthesis and Physical Properties

Abstract: This report describes the synthesis of ionic liquids that incorporate the N-methyl-2-hydroxyethylammonium cation with various carboxylic acid anions and the study of some of their physical properties, including self-diffusion coefficients, density, speed of sound, viscosity, and refractive index. 1 H and 13 C NMR spectra were used to characterize the chemical structure of the species in concordance with FT-IR spectra. DOSY NMR spectra was used to determine the self-diffusion coefficients of the components, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 19 publications
1
85
0
3
Order By: Relevance
“…Their properties of extremely low vapor pressure, high viscosity, high thermal and ionic conductivity, non-flammability, thermal and chemical stability, and low toxicity make them suitable in many fields of applications, such as catalysis, electrochemical devices and separation processes. Protic ionic liquids can be tailored for a specific application taking into account that a small change whether in anion structure whether in cation structure or in both, modifies their corresponding physicalchemical properties [1][2][3][4][5][6][7] . Among the promising uses of ionic liquids, lubrication for metal-metal, metal-ceramic and ceramic-ceramic contacts has been a new trend since the authors Ye et al 8 showed a significant reduction in the average coefficient of friction for some of the aforementioned tribopairs using two different alkylimidazolium tetrafluoroborates.…”
Section: Introductionmentioning
confidence: 99%
“…Their properties of extremely low vapor pressure, high viscosity, high thermal and ionic conductivity, non-flammability, thermal and chemical stability, and low toxicity make them suitable in many fields of applications, such as catalysis, electrochemical devices and separation processes. Protic ionic liquids can be tailored for a specific application taking into account that a small change whether in anion structure whether in cation structure or in both, modifies their corresponding physicalchemical properties [1][2][3][4][5][6][7] . Among the promising uses of ionic liquids, lubrication for metal-metal, metal-ceramic and ceramic-ceramic contacts has been a new trend since the authors Ye et al 8 showed a significant reduction in the average coefficient of friction for some of the aforementioned tribopairs using two different alkylimidazolium tetrafluoroborates.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36][37] In order to clarify solvent natures, one must have extensive knowledge of physicochemical and Brønsted and/or Lewis acid-base properties of ionic liquids. Experimental results for the physicochemical properties [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] and solvatochromic parameters [53][54][55] of ionic liquids with the hydroxyl groups have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[63] Subsequently, a series of substituted amine-based ILs with the aliphatic linear pentanoic acid as counter anion was prepared. [64] In particular, (2-hydroxyethyl)ammonium pentanoate [HOH 4 COO] were synthesized and the influence of their structural variations on their thermodynamic properties (density, ultrasonic velocity, ionic conductivity, refractive index, viscosity, and surface tension) was investigated as a function of temperature.…”
Section: N][hcoo]mentioning
confidence: 99%
“…[63] The sizes and types of alkyl chain also determine the effect of temperature on some physico-chemical properties; local structure models should be applied to explain the macroscopic behavior in terms of the molecular arrangement.…”
Section: Acidity and Structural Organization Of Brønsted Acidic Ilsmentioning
confidence: 99%